Estilha?os da cidade: uma leitura de Eles eram muitos cavalos, de Luiz Ruffato - Silva, Amanda Trindade Martins da (2017)
There were many horses, by Luiz Ruffato, a work published for the first time in 2001 by the publisher Boitempo, is considered one of the most instigating narratives of contemporary brazilian literature. From this work, its author has received several awards and emerged as one of the great names of urban fiction, being one of the most referenced, translated and studied in the last decade. Fragmentary and shattered, the novel is composed of innumerable possibilities of language, becoming a hybrid work and that instigates curiosity and analysis. The present study objective formulate questions and answers that explain how the urban complexity of modernity is represented in the novel. For this, an approach is divided into parts, separating the representative nucleus into the shapes of the characters and plots that appear in the short 69 chapters, arranged as shards of a mosaic of situations. Initially considerations are made about contemporary literature and about the writer Luiz Ruffato. Then, reflections will be woven on the situations and impasses experienced by the urban population, with their perspectives and their dramatic unfolding. Later, the minority share enters the center of the discussions, focusing on the female characters and then on the black and indigenous figures. Finally, several situations are mentioned that are used by the author as artifices to compose the work and, in addition, the idea defended by Luiz Ruffato himself as his book a literary installation. For this the contributions of theorists Karl Erik Schollhammer, Ant?nio C?ndido, Mikhail Bakhtin, Renato Cordeiro Gomes, N?stor Garc?a Canclini, Zygmunt Bauman, Antoine Compagnon, Alfredo Bosi, ?tienne Souriau will be fundamental for the development of this research.